Figure 4 from: Costa AF, Siciliano S, Emin-Lima R, Martins BML, Sousa MEM, Giarrizzo T, Silva Júnior JS (2017) Stranding survey as a framework to investigate rare cetacean records of the north and north-eastern Brazilian coasts. ZooKeys 688: 111-134. https://doi.org/10.3897/zookeys.688.12636 - Costa, Alexandra Fernandes; Siciliano, Salvatore; Emin-Lima, Renata; Martins, Bruna Maria Lima; Sousa, Maura Elisabeth Moraes; Giarrizzo, Tommaso; Silva Júnior, José de Sousa e (Zenodo, 2017)
Figure 4 - Stranding events: small and medium-sized cetaceans. a The carcass of a Fraser's dolphin, Lagenodelphis hosei was cut down on the village of Carnaubeira, Araioses municipality (2°42.6'S, 42°0.6'W) and consumed locally (photo PROCEMA files) b A group of 12 live Guiana dolphins Sotalia guianensis were found trapped (photo showed just one specimen) in a tidal channel alongside Corvina beach, Salinópolis municipality, eastern Pará (0°36'S, 47°22.2'W) c A False killer whale Pseudorca crassidens stranded on the north-eastern coast of Pará, Praia de Marudá, Marapanim municipality (photo GEMAM files) d A Short-finned pilot whale Globicephala macrorhynchus stranded in advanced stage of decomposition at Praia da Pedra do Sal, Parnaíba municipality (2°40.8'S, 42°31.2'W), the shape of the head and number of teeth were diagnostic to identify the species (photo PROCEMA files).